Protocol for an observation and implementation study investigating optimisation of the management of stroke and transient ischaemic attack (TIA) - Sheppard, J; Mellor, R; Bailey, S; Barton, P; Boyal, A; Greenfield, S; Jowett, S; Mant, J; Quinn, T; Singh, S; McManus, R (BMJ Publishing Group, 2012)
INTRODUCTION: Patients benefit from early and intensive treatment in both acute ischaemic stroke and transient ischaemic attack. Recent audits of acute stroke/transient ischaemic attack care suggest that although standards have improved, current services still fall short of optimal care. The aim of this study is to establish a database of patients accessing stroke services. Data will be collected and analysed to provide individualised feedback to healthcare professionals who can then use these findings to develop strategies for service improvement. METHODS AND ANALYSIS: This longitudinal observational study will evolve with the ongoing findings from the research output. The project will consist of three phases: assessment of current practice, feedback of findings and evaluation of service change. Consecutive patients will be recruited from participating hospitals, and identifiable data will be collected to link records from the Primary Care, Secondary Care and Emergency Services. As this study focuses on observation of current practice, a sample size calculation is not deemed appropriate. Patients will be sent follow-up questionnaires examining quality of life at 3 and 12 months post-event. Qualitative interviews will examine the care pathway through the experiences of patients, their carers, healthcare personnel and commissioners. Collected data will be used in economic analyses, which will evaluate the impact of current care and service redesign on the NHS costs and patient outcomes (death and quality of life). ETHICS AND DISSEMINATION: Ethical approval for this study has been obtained from the National Research Ethics Committee (reference; 09/H0716/71), and site-specific RandD approval has been acquired from the relevant NHS trusts. All findings will be presented at relevant healthcare/academic conferences and written up for publication in peer-reviewed journals. Results will be fed back to patients and participating trusts through a series of reports and presentations. These will be used to facilitate discussions about service redesign and implementation.